Измерение индекса демократии как предпосылка управления процессом демократизации (Украина и посткоммунистические страны Центральной и Восточной Европы, 1994–2004) - Зельницкий, А. (Социология: теория, методы, маркетинг, 2004)
The author analyzes the most famous approaches to identification of indices of democratization in post-communist states of Central and Eastern Europe at macro and micro-levels. Such approaches are the first step towards development of original comprehensive quality–quantity evaluation of democratic processes. The purpose of this methodology is not only to get an integral indicator, but to facilitate control of these processes, making them more sustainable and dynamic.